Peran Keterlibatan Digital Dalam Menjembatani Technostress terhadap Kinerja Strategis Aparatur Sipil Negara - Neng Evi Kartika; Ilham Akbar; Aris Budiman (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
The digital transformation in public sector organizations requires civil servants to adapt to ever-evolving technologies. However, technology-induced work pressure, known as technostress, may negatively impact their strategic job performance if not managed effectively. This study aims to examine the effect of technostress on strategic job performance, with digital work engagement as a mediating variable. The research involved 94 civil servants from two local government agencies using a quantitative approach. Data were collected through a structured Likert-scale questionnaire. The results revealed that technostress had a significant negative effect on strategic job performance, while digital work engagement showed a significant positive effect. Mediation testing using the Sobel test confirmed that digital work engagement significantly mediated the relationship between technostress and strategic job performance. These findings emphasize the importance of fostering digital work engagement as a strategy to mitigate the negative impact of technostress within civil service environments.